Efektivitas Perlindungan Atas Upah Sebagai Hak Tenaga Kerja Outsourcing di Kota Batam - Rusdiana, Shelvi; Jaya, Febri; Simatupang, Evlyn Grace (Universitas Medan Area, 2023)
Outsourcing is a practice in the business world that has emerged since the late 80s and has become the main business strategy in a climate of increasingly fierce competition. Defined as a process of outsourcing or moving or buying up business activities to third parties, the main and foremost purpose of outsourcing is to save production costs. The purpose of this study is to determine the effectiveness of wage protection for outsourced labor rights in Batam and to find out how outsourced labor in practice in the field. This research uses empirical legal research methods using qualitative descriptive research types. The results of this study show that legal protection of wages as labor, especially the protection of the rights of outsourced labors in Batam, has not been optimal or effective. This is evidenced by the large number of outsourced labor workers who do not get their rights, especially not getting a decent salary. Outsourcing labor has created exploitative, discriminatory, degradative and fragmentative working conditions and is effective at weakening the power of trade unions. Such a situation needs to be corrected so that there is a balance between the interests of workers, employers and the government. The government is the main actor that must play a role in creating this balance. Regulatory factors in the form of laws and regulations made are very open to diversity of interpretations, very weak law enforcement, lack of quality and number of officers disnakertrans, unbalanced bargaining position of unions against employers. Another important condition that also causes labor losses is the lack of health insurance, work injury insurance, retirement insurance, old age insurance have not been established as tools to safeguard outsourced labors.